Diet and disturbance: Seaside Sparrow resource use driven by oiling and Hurricane Isaac - Snider, Allison M.; Bonisoli-Alquati, Andrea; Pérez-Umphrey, Anna A.; Woltmann, Stefan; Stouffer, Philip C; Taylor, Sabrina S. (Frontiers in Environmental Science, 2022)
The 2010 Deepwater Horizon (DWH) disaster led to extensive oil deposition in Louisiana’s coastal wetlands, followed two years later by Hurricane Isaac. These disturbances led to changes in saltmarsh invertebrate communities, potentially affecting higher-level predators and the saltmarsh food web. Seaside Sparrows (Ammospiza maritima) are ubiquitous, year-round residents of the coastal saltmarsh affected by the DWH spill, where they consume diverse invertebrates and may be considered an indicator species for the ecosystem’s integrity. We used DNA metabarcoding to evaluate prey consumed by Seaside Sparrows to understand how sparrows responded to residual contamination from the DWH oil spill and ecosystem disturbance caused by Hurricane Isaac. To do so, we evaluated metrics of diet (prey richness, diversity, overall diet composition) and resource use (total niche width, individual specialization) from 2011-2017 on oiled, unoiled, and reference sites. We found that while diet composition varied across years and site type, Hurricane Isaac had an even greater effect on the richness and diversity of prey consumed. Resource use—as measured by the total niche width of the populations and degree of individual specialization—was most stable on unoiled sites compared to unoiled and reference sites. Finally, we analyzed resource use for each combination of site type and year (i.e.: “2014 oiled sites”), which indicated a strong correlation between individual specialization and total niche width: as total niche width increased, individuals became more specialized, following the predictions of the Niche Variation Hypothesis.